The Effect of Students' Perceived Social Presence in Distance Learning on Their Willingness to Attend Online Guidance with Improved Social Presence: The Mediating Role of Usefulness, Utility, Chance, and Behavioral Intention - Mudafiatun Isriyah; Hariyanto Hariyanto; Nasruliyah Hikmatul Maghfiroh; Addahri Hafidz Awlawi; Hastiani Hastiani (Bulletin of Counseling and Psychotherapy, 2023)
Four independent variables, social Presence, ease of use, usability, and risk, significantly affect students' intentions to interact in online tutoring on the Website. Social Presence is the dominant variable influencing students' intentions to interact virtually. These findings bring some implications for the distance learning management team that adopts the Website as their media. Social presence factors affect online guidance and counseling. It is analyzed from the potential of technological development, which is the purpose of this study to see the effect of social presence on the implementation of online guidance-the method used is multiple linear regression analysis, where this study identifies independent variables that affect the dependent variable through multiple regression hypotheses with 80 respondents. This study found that perceived social presence, utility, usefulness, and opportunity significantly influenced behavioral intention on online guidance by increasing social presence. In addition, behavioral intention was observed as the most dominant variable affecting students' intention to interact in distance learning.